2011
DOI: 10.1002/btpr.580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of steam‐treated giant bamboo for production of fermentable sugars

Abstract: Giant bamboo plantations are currently being established in the Southern Africa region and can be considered as potential lignocellulosic feedstock for the production of second generation bioethanol. In this study, giant bamboo internodal material was subjected to sulphur dioxide (SO(2)) impregnated steam pretreatment prior to enzymatic hydrolysis. The effect of temperature, residence time, and acidity on the overall sugar recovery and byproduct formation was studied using response surface response technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
(51 reference statements)
3
19
0
Order By: Relevance
“…Other potential fermentation inhibitors, including furfural derived from pentoses, HMF from degradation of hexoses, and levulinic and formic acids from successive decomposition of HMF were not detected in the spent liquors. The total inhibitors were in lower concentrations in spent liquor than acid or steam pretreated spent liquors [14,15]. The concentration of acetic acid which released from acetyl groups on hemicelluloses was higher than acid pretreated spent liquor.…”
Section: Fermentation Inhibitorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Other potential fermentation inhibitors, including furfural derived from pentoses, HMF from degradation of hexoses, and levulinic and formic acids from successive decomposition of HMF were not detected in the spent liquors. The total inhibitors were in lower concentrations in spent liquor than acid or steam pretreated spent liquors [14,15]. The concentration of acetic acid which released from acetyl groups on hemicelluloses was higher than acid pretreated spent liquor.…”
Section: Fermentation Inhibitorsmentioning
confidence: 86%
“…They may be divided up into the following broad categories: construction and reinforcing fibers; paper, textiles and board; food; combustion and other bioenergy applications [2]. Due to its advantages of fast growth, short renovation, and easy propagation, more and more attention has been paid to the applications in biobased energy field including bioethanol production [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In pretreatment of vineyard pruning by uncatalyzed steam explosion (Buratti et al, 2015), optimal conditions were observed at severity of 4.24, obtaining an overall sugar yield of 42.5%. In steam explosion pretreatment of giant bamboo, Garcia-Aparicio et al (2011) reported the overall sugar yield of 81.2% under optimal conditions of 2.5% sulfuric acid impregnation and severity of 4.13.…”
Section: Optimization Of Overall Sugar Yieldmentioning
confidence: 98%
“…Relatively few studies have reported on the application of steam explosion with lignocellulosic feedstock, like olive tree pruning , vineyard pruning (Buratti et al, 2015), and giant bamboo (Garcia-Aparicio et al, 2011), evaluating the overall sugar yield. According to Cara et al (2008), the optimum treatment conditions of olive tree pruning for maximizing overall sugar yield (63.4%) were 1% sulfuric acid impregnation and severity of 4.53.…”
Section: Optimization Of Overall Sugar Yieldmentioning
confidence: 99%
“…Some researchers have focused on bamboo pretreatment for bioethanol production. The cellulose conversion to glucose yield of bamboo is lower than that of both wood and agricultural waste (Shimokawa et al 2009;Leenakul and Tippayawong 2010;García-Aparicio et al 2011;Li et al 2014).…”
Section: Introductionmentioning
confidence: 94%